THE ROLE OF USING REAL OBJECT MEDIA IN EXPLAINING ELECTRICAL CIRCUITS TO PHYSICS STUDENTS OF JABAL GHAFUR UNIVERSITY - Hamdi Hamdi; Muhammad Saiful (Bajang Institute, 2023)
One of the media that can be used in learning physics in the Physics Study Program is the tools available in the laboratory. This research was carried out at the Physics Study Program at Jabal Ghafur University entitled ““The Role of Using Real Material Media in Explaining Electrical Circuits to Physics Students at Jabal Ghafur University. The use of media in the physics learning process is a demand in the curriculum. Media in the learning process can be used in the form of original objects or in the form of pictures. Formulation of the problem: